If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4x + -3) + 9x = -7 Reorder the terms: -5(-3 + 4x) + 9x = -7 (-3 * -5 + 4x * -5) + 9x = -7 (15 + -20x) + 9x = -7 Combine like terms: -20x + 9x = -11x 15 + -11x = -7 Solving 15 + -11x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -11x = -7 + -15 Combine like terms: 15 + -15 = 0 0 + -11x = -7 + -15 -11x = -7 + -15 Combine like terms: -7 + -15 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| -18=-20a | | 5x+1/6+2x+1/3=2 | | -(3y-2)= | | 5x+10+6x-4=180 | | 4(2a+3b)-3(a+2b)= | | 4squared+x=w | | 70+[(-117)+(-72)]= | | 1/2+11/3= | | 1/2+1*1/3= | | 20X^3-180x^2=0 | | 7t+8(5-3t)= | | 1/2+1.1/3= | | 2(r-1)+3(4+r)= | | (-20)+139= | | x+2.3-5.4=4.8 | | 70+[(-117)+(-78)]= | | 10-3w-5+x=25 | | y+15=-7 | | 6x-4=5x-30 | | 12+[5+(-7)]= | | F(x)=6x+9 | | [-1+(-8)]+[3+(-1)]= | | (m+5)-19=-13 | | 3(c+1)-15+c= | | 19+(-10)+(-14)= | | 163+14+(-90)= | | y-9=50 | | 4x(6x-5)= | | [-15+(-10)]+6= | | 5kgu=0.1 | | 1.5y+3.5(2+y)= | | .2(x-5)=20 |